Challenges of Implementing Big Data Technology in Higher Institutions - Mercy Mwangala Ziezo; Jude Odiakaosa Osakwe; Martin M Ujakpa; Gloria E Iyawa (Journal of Information System and Informatics, 2021)
The aim of this study is to investigate the challenges of implementing Big Data Technology (BDT) in Higher Educational Institutions (HEIs) in Namibia. The study further undertook quantitative surveys with staff of the three (3) higher institutions in Namibia. A sample of 345 participants from International University of Management (IUM), Namibia University of Science and Technology (NUST), and The University of Namibia comprising the study's population (UNAM) were selected for this study using the simple random sampling technique. The data collected was analysed for descriptive statistics using the Statistical Package for Social Sciences (SPSS). The finding indicated that there are challenges such as lack of awareness of BDT, lack of support for management and inadequate IT infrastructure. The study further recommended strategy that will enhance the implementation of BDT in HEIs.